Insect vectors of cowpea mosaic virus in Nigeria - Whitney, W.K.; Gilmer, R.M. (Wiley, 1974)
A yellow strain of cowpea mosaic virus (CPMV) was transmitted in cowpea by two thrips, Sericothrips occipitalis and Taeniothrips sjostedti; two chrysomelid beetles, Ootheca mutabilis and Paraluperodes quaternus; a curculionid beetle, Nematocerus acerbus; and two acridid grasshoppers, Catantops spissus spissus and Zonocerus variegatus. Summarizing trials with single insects, the efficiency of transmission of CPMV averaged 18—21% for N. acerbus and the two grasshoppers, 55% for P. quaternus, and 71% for O. mutabilis. Twenty‐two and 40% of the plants exposed to large populations of S. occipitalis and T. sjostedti, respectively, were infected. In three trials with an aphid, Aphis craccivora, 4 of 49 plants were infected with CPMV, but these infections were considered spurious because no infections occurred in any of 63 plants exposed to this insect in four other trials. A coreid bug, Riptortus dentipes, did not transmit CPMV. Mosaic symptoms in infected plants appeared 5—39 days after they were exposed to vectors. Infective virus was recovered from fresh faecal pellets of each grasshopper vector.